The effect of social media advertising on consumer purchasing decision "A Survey Study" - Zaher, Bassam; Arous, Helen (Latakia University Journal - Economic and Legal Sciences Series, 2020)
The purpose of this research is to investigate the effect of social media advertising on consumer purchasing decision, and to determine the effect of each dimension of advertising on consumer purchasing decision. The study was conducted in real estate consumers in Lattakia city. The study results shows that advertising on social media affects the purchasing decision of the consumer as there is a positive relationship between them, and that the most influential dimension of the advertising on the purchasing decision is the characteristics of the advertising followed by the design of the advertising and then the content of the advertising message. هدفت الدراسة إلى معرفة تأثير الإعلان عبر شبكات التواصل الاجتماعي على القرار الشرائي للمستهلك وتحديد تأثير كل بُعد من أبعاد الإعلان على القرار الشرائي للمستهلك. وتمت الدراسة على مستهلكي العقارات في مدينة اللاذقية. وتوصلت الدراسة إلى أن الإعلان عبر مواقع التواصل الاجتماعي يؤثر على القرار الشرائي للمستهلك حيث أن هناك علاقة إيجابية بينهما، وأن أكثر بُعد من أبعاد الإعلان تأثيراً على القرار الشرائي هو خصائص الإعلان يليه تصميم الإعلان ومن ثم محتوى الرسالة الإعلانية.